PENGEMBANGAN MODUL BERBASIS INKUIRI UNTUK PEMBELAJARAN MENULIS CERITA PENDEK DI SMA NEGERI 8 KOTA JAMBI - Kris Arta Maria Hutabarat; Afif Rofii; Supriyati Supriyati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to develop an inquiry-based short story writing learning module that is valid, practical, and effective for use by 11th-grade students of SMA Negeri 8 Kota Jambi. This research uses a Research and Development (R&D) approach with the 4-D model (Define, Design, Develop, and Disseminate). The research subjects included linguistic experts, content feasibility experts, design experts, an Indonesian language teacher, and 11th-grade students. Data collection instruments consisted of validation questionnaires, practicality questionnaires, and learning outcome tests. The data were analyzed using descriptive qualitative and quantitative methods. The results of the content feasibility validation obtained a percentage of 92%, content presentation validation 84.62%, linguistic validation 100%, and graphic design validation 97.14%, all categorized as highly valid. The practicality test showed an average teacher response percentage of 88% and a student response of 85.92%, both categorized as highly practical. The effectiveness test based on student learning outcomes showed that 100% of the students achieved the Minimum Completeness Criteria (KKM ≥ 70), with an average score of 84.39, indicating that the module is highly effective. Therefore, this inquiry-based learning module is highly feasible to be used as teaching material to improve students' short story writing skills